Viability Test of Collagen Extract from Gouramy Scale (Oshpronemusgouramy) on Bone Marrow Mesenchymal Stem Cell Culture (Medico Legal Update, 2020)
Background: The role of type I collagen is as a matrix of extracellular proteins with characteristics ofincreased cell proliferation which directly affects the physiology and morphology of cells. Type 1 collagencan be obtained from fish scales. Thus, this research aimed to support engineering tissue used for thetreatment of periodontal disease in the regenerative surgery by utilizing collagen derived from gouramyscales. As an initial step, the researchers wanted to conduct a study used collagen extract derived fromgouramy scales (Osphoronemusgouramy) which was applied to bone marrow mesenchymal stem cellcultures to see viability in vitro.Objective: To determine the viability of collagen from fish scales (Osphronemusgouramy) to bone marrowmesenchymal stem cells. Method: Bone marrow mesenchymal stem cells are taken from mice and plantedin 96 well plates. Collagen extracted from gouramy scales using the enzymatic method was dissolved in acondition medium with each concentration of 0.01 mg/ml, 0.02 mg/ml, 0.04 mg/ml, 0.16 mg/ml, 0.32 mg/ml was put into the well prepared and incubated for 24 hours for the MTT assay.Result: Collagen from fish scales can increase the viability of bone marrow mesenchymal stem cells witha percentage above 90% and the highest viability concentration at 0,01 mg/ml. Conclusion: Collagen fromfish scales is viable against bone marrow mesenchymal stem cells. Collagen scales of gouramy soaked inmedium had the highest viability with an optimum dose of 0.01 mg/ml.